Comparative Adsorption of Copper Ion (Cu2+) onto Raw and NaOH-Modified Coal Fly Ash at Various Initial Concentrations - Ilham Aswi Syaputra; Farrah Fadhillah Hanum; Aster Rahayu; Rimadina Sukmasuci Lestari (Journal of Chemical Natural Resources, 2025)
Coal fly ash, a voluminous industrial solid by-product generated during coal combustion in thermal power facilities, has garnered considerable scientific attention as a cost-efficient sorption material for eliminating heavy metal contaminants from industrial effluents. This study comparatively evaluates the adsorption performance of unmodified coal fly ash (FA) and NaOH-modified coal fly ash (FA-NaOH) for Cu²⁺ removal from synthetic wastewater using a batch system. Both adsorbents were characterized for moisture content and iodine adsorption capacity. Equilibrium sorption experiments were conducted across a Cu²⁺ initial concentration of 25–125 mg/L using 7.5 g of adsorbent in 200 mL solution at 500 rpm for 60 minutes at room temperature. Residual copper was analyzed by Atomic Absorption Spectrophotometry (AAS). The FA-NaOH consistently outperformed FA, achieving removal efficiencies between 83.01% and 99.98%, and a maximum adsorption capacity (qm) of 2.4325 mg/g compared to FA 2.3250 mg/g. The equilibrium data for adsorption aligned better with the Langmuir isotherm (R² = 0.9077), particularly for FA-NaOH, indicating monolayer adsorption at homogeneous active sites. These results collectively affirm that alkaline activation markedly amplifies the Cu²⁺ uptake capacity of coal fly ash, confirming NaOH-modified coal fly ash as an economically accessible and ecologically sound strategy for heavy metal removal in wastewater treatment.